2020
DOI: 10.3390/microorganisms8081205
|View full text |Cite
|
Sign up to set email alerts
|

Differential miRNA-Gene Expression in M Cells in Response to Crohn’s Disease-Associated AIEC

Abstract: Adherent-invasive Escherichia coli (AIEC), which abnormally colonize the ileal mucosa of Crohn’s disease (CD) patients, are able to invade intestinal epithelial cells (IECs) and translocate through M cells overlying Peyer’s patches. The levels of microRNA (miRNA) and gene expression in IECs and M cells upon AIEC infection have not been investigated. Here, we used human intestinal epithelial Caco-2 monolayers and an in vitro M-cell model of AIEC translocation to analyze comprehensive miRNA and gene profiling un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…A Systems Biology Approach to Identify Novel Biomarkers in Progression from Crohn's Disease to Colorectal Cancer factors (Larabi et al, 2020;Liu et al, 2015). Results of genome-wide association studies indicated that several genes have a role in inheritable vulnerability to CD.…”
Section: Research Articlementioning
confidence: 99%
“…A Systems Biology Approach to Identify Novel Biomarkers in Progression from Crohn's Disease to Colorectal Cancer factors (Larabi et al, 2020;Liu et al, 2015). Results of genome-wide association studies indicated that several genes have a role in inheritable vulnerability to CD.…”
Section: Research Articlementioning
confidence: 99%
“…Various innate and adaptive immune cells are present in PPs including conventional B and T cells, plasma cells, CD4 + TCR-β + T-cells and γδ T-cells [74,75]. PPs have been shown to play an important role in the initiation of mucosal inflammation in patients with CD and in murine models, since bacteria, especially the adherent-invasive E.coli (AIEC) colonizing the PPs subepithelial dome, interact with resident DCs and, hence, acquire an inflammatory profile with elevated TLR-4 and TNF-a expression [76][77][78][79]. Th1 polarization has also been observed in the PPs of patients with active as compared to inactive CD, UC and healthy controls [80].…”
Section: The Involvement Of Peyer's Patches and Colonic And Cecal Pat...mentioning
confidence: 99%
“…Larabid et al. (2020) analyzed the dysregulated miRNAs and their potential target genes in AIEC infection of Caco-2-cl1 cells, and downregulated miR-31c-1-3p may target mucins ( MUC1) and claudin ( CLDN ) to disturb the intestinal barrier function of IBD patients ( 47 ). Moreover, a previous study had indicated that AIEC reduced expression of proteins required for autophagy through upregulating miR-30c and miR-130a in T84 cells and mouse enterocytes, thus conducting self-replication ( 6 ).…”
Section: Mirnas and Intestinal Epithelial Barrier In Ibdmentioning
confidence: 99%